Fleksibilitas Tanpa Batas: Analisis Kualitatif Beban Psikologis Dan Kesejahteraan Subyektif Pekerja Kreatif Digital Di Denpasar - Wahyu Bagas Kinandana; I Putu Dharmawan Pradhana; Ni Ketut Anjani; Putu Purnama Dewi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The shift from conventional tourism to digital creative economy in Denpasar has created a dynamic yet vulnerable class of digital creative workers facing glorified work flexibility. This study aims to explore the phenomenological experiences of digital creative workers (photographers, videographers, graphic designers) regarding psychological burden and subjective well-being (SWB). Employing a qualitative transcendental phenomenology approach, data were gathered from eight key informants in Denpasar via purposive and snowball sampling, using in-depth interviews, participant observation, and document analysis. Data analysis followed phenomenological reduction, noematic-noetic analysis, and essence synthesis, enhanced by source triangulation. Findings reveal the